2016
DOI: 10.1245/s10434-015-5070-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymph Node Ratio in Metastatic Cutaneous Squamous Cell Carcinoma of the Head and Neck

Abstract: LNR is potentially an independent predictor of outcome in patients with metastatic cutaneous nodal SCC. The clinical relevance of this finding requires further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…The regional recurrence rate of our study was 18%, compared to 33% (Mizrachi et al and 12% (Tseros et al. Our study population had a greater proportion of poorly differentiated tumors (34%) than Tseros et al (26%). Interestingly, only 63% of patients had adjuvant radiotherapy in our study compared with 92% reported by Tseros et al, which reflects our institutional bias toward a more selective use of adjuvant therapy and higher number of salvage cases.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The regional recurrence rate of our study was 18%, compared to 33% (Mizrachi et al and 12% (Tseros et al. Our study population had a greater proportion of poorly differentiated tumors (34%) than Tseros et al (26%). Interestingly, only 63% of patients had adjuvant radiotherapy in our study compared with 92% reported by Tseros et al, which reflects our institutional bias toward a more selective use of adjuvant therapy and higher number of salvage cases.…”
Section: Discussioncontrasting
confidence: 58%
“…As a quaternary referral center for advanced head and neck disease, we also see more aggressive disease, as reflected in the greater number of positive nodes (n = 4) in our cohort compared to Tseros et al (n = 2.5) and Mizrachi et al (n = 2.2). The regional recurrence rate of our study was 18%, compared to 33% (Mizrachi et al and 12% (Tseros et al. Our study population had a greater proportion of poorly differentiated tumors (34%) than Tseros et al (26%).…”
Section: Discussionsupporting
confidence: 54%
“…The LNR expresses the ratio of involved lymph nodes to the total number of lymph nodes removed and has become a well‐recognized prognostic factor in many cancer types. Several studies have suggested the LNR is also an independent prognostic factor in metastatic cSCCHN . Tseros et al .…”
Section: Discussionmentioning
confidence: 99%
“…One factor that has received limited attention is the prognostic significance of the number of nodal metastases, with the literature to date reporting conflicting results . However, recent studies have shown that the lymph node ratio (LNR) is an independent prognostic factor in metastatic cSCCHN . This raises the possibility that the number of metastatic lymph nodes, the numerator in the LNR, may be of importance beyond the single versus multiple node distinction currently used in the American Joint Committee on Cancer (AJCC) nodal (N) staging system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation